Future Power Plant Portfolio Analysis from the Point of View of Minimum Cost and Emission Optimization - Bozsik, Nándor (International Journal of Engineering and Management Sciences, 2024)
The article examines the expected composition of the power plant portfolio in Hungary by 2030. The indicators considered are the life-cycle unit costs (LCOE) and the life-cycle specific carbon dioxide emissions (LCA(CO2)) of the power plant types. The minimum of these two indicators, as objective functions, is determined by a linear programming method for the power plant portfolio. The results show that the LCOE minimum for the power plant portfolios in 2030 is worse in absolute terms and better in specific terms than in 2021. In both absolute and specific terms, the LCA(CO2) minimum is more favourable in 2021. These results are met under the thirty and twenty-five percent electricity import scenarios. With twenty percent imports, the absolute values are worse and the specific values are better for both indicators. On the other hand, the results of the calculations for 2030 fall short of the 2030 Agenda of the Institute for a Green Transition. This is due to the delay in commissioning a new nuclear power plant and the transformation of industry with increasing electricity demand. For the portfolios under review, a minimum of thirty percent of domestic generation from renewable sources is met. This contributes significantly to the European Union’s ambition for the sector to be net greenhouse gas-free by 2050.